YOUTH VOTER ORIENTATION IN BALI IN THE 2024 PRESIDENTIAL ELECTION - Ni Luh Putu Suciptawati; Karolien Miracle Anggraeni (Adisam Publisher, 2026)
This study aims to analyze the orientation of young voters in the 2024 Presidential Election using a cross-tabulation approach across various demographic and social variables. The research employs a quantitative methodology with Chi-square test analysis to examine relationships among variables. The sample consists of 595 respondents from Generation Z and Millennials. The results indicate that gender, occupation, and education have a significant influence on preferences for presidential and vice-presidential candidate pairs. Specifically, Candidate Pair No. 2 dominates support across nearly all categories. In contrast, age and organizational participation show no significant effect on respondents’ choices. These findings suggest that the political orientation of young voters is more strongly influenced by socio-political background and educational level than by age or organizational experience.